Finerenone in Diabetic-Kidney Disease, True Result Renal and Cardiovascular Outcome: A Meta-Analysis - Felicita Gracia; Arya Marganda Simanjuntak; Samira Amanda; Linda Ida Mustika; Juwanto; Ligat Pribadi Sembiring; Jazil Karimi; Sari Harahap; Rosmaliana (Aesculapius Medical Journal, 2026)
Abstract Diabetic kidney disease (DKD) is a major complication of type 2 diabetes, increasing cardiovascular risk. Existing treatments leave significant residual progression risk. Finerenone, a novel nonsteroidal mineralocorticoid receptor antagonist, shows promise. This meta-analysis evaluates finerenone's effects on renal and cardiovascular outcomes in DKD. A Systematic Review and Meta-Analysis (PROSPERO CRD420251122382) followed PRISMA guidelines. PubMed, ScienceDirect, and Epistemonikos utilized and used keywords "Finerenone AND Diabetes AND Chronic Kidney Disease AND Outcomes." RCTs comparing finerenone to placebo in DKD, reporting renal or cardiovascular outcomes, were included. Data extraction covered study characteristics and outcomes. RevMan 5.4 analyzed data using a random-effects model. Risk of bias (RoB2) and certainty of evidence (GRADE-PRO) were assessed. Three RCTs (19,027 participants) were included for renal outcomes, and two RCTs (13,026 participants) for cardiovascular outcomes. Finerenone significantly reduced odds of sustained eGFR decline ?40% (OR 0.83, p=0.0003), ?57% (OR 0.86, p=0.0001), and the major composite kidney outcome (OR 0.76, p<0.0001). ESKD odds reduction (21%) was not statistically significant. For cardiovascular outcomes, finerenone significantly reduced hospitalization for heart failure (OR 0.78, p=0.0001). Trends towards reduced cardiovascular death (OR 0.88, p=0.09) were noted. Studies had low bias risk, and most outcomes showed moderate evidence certainty.Finerenone offers robust renoprotection and significantly reduces heart failure hospitalizations in DKD. finerenone as a key nonsteroidal mineralocorticoid receptor antagonist for comprehensive management, improving both renal and cardiovascular outcomes in this high-risk group. Keywords: chronic kidney disease, cardiovascular, diabetes, finerenone, renal.